Revisiting the binary azeotropic separation containing tetrahydrofuran and ethanol: Design and control of extractive distillation using dimethyl sulfoxide as alternative solvent - Kong, Zong Yang; Yang, Ao; Saptoro, Agus; Sunarso, Jaka (ScienceDirect, 2022)
This study reexamined the possibility of improving the separation of binary azeotropic mixture containing tetrahydrofuran (THF) and ethanol from previous work (J Chem Technol Biotechnol 2015; 90: 1463–1472) that rely on the extractive distillation (ED) using ethylene glycol (EG) as solvent. Here, dimethyl sulfoxide (DMSO) is proposed as an alternative solvent for the ED, and its feasibility is preliminary screened and compared against the usage of EG. The conceptual ED using DMSO is designed by manipulating all the design variables until the minimum product specifications (i.e. purity) are achieved. Then, the conceptual design is further optimised using particle swarm algorithm to obtain the ideal column configuration and the performance is compared against the ED using ethylene glycol (EG) and pressure swing distillation (PSD) (i.e. best process) from previous work based on economic and CO2 emission. Overall, the optimised ED using DMSO provides 36% and 37% lower economic and CO2 emission with respect to the ED using EG. In comparison to PSD (i.e. best process) from previous work, it provides 24% and 25% reduction in TAC and CO2 emission. Lastly, a control structure is developed for the proposed ED using DMSO that can effectively handle ± 10% throughput and ± 5% feed composition disturbances without the need of a composition controller as in the case of previous work.